2016
DOI: 10.1016/j.jbiomech.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing nutrient channel spacing and revisiting TGF-beta in large engineered cartilage constructs

Abstract: Cartilage tissue engineering is a promising approach to treat osteoarthritis. However, current techniques produce tissues too small for clinical relevance. Increasingly close-packed channels have helped overcome nutrient transport limitations in centimeter-sized chondrocyte-agarose constructs, yet optimal channel spacings to recapitulate native cartilage compositional and mechanical properties in constructs this large have not been identified. Transient active TGF-β treatment consistently reproduces native com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…While channels appear promising during short term culture, we and others have shown that macro-channels can become filled with newly formed tissue early in culture (Supplementary 2). This can be addressed to some extent by ‘re-punching’ the closed channels [21], though this requires an additional handling step during culture. To overcome this limitation, in this study we included a porous HF or a HF strung with a cotton thread to maintain channel patency and improve nutrient/waste transport into the core of the construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While channels appear promising during short term culture, we and others have shown that macro-channels can become filled with newly formed tissue early in culture (Supplementary 2). This can be addressed to some extent by ‘re-punching’ the closed channels [21], though this requires an additional handling step during culture. To overcome this limitation, in this study we included a porous HF or a HF strung with a cotton thread to maintain channel patency and improve nutrient/waste transport into the core of the construct.…”
Section: Discussionmentioning
confidence: 99%
“…This again suggests that the edge of the construct develops the highest properties and dominates both bulk and local mechanical response in constructs of this size. This may in the future be addressed by adding additional nutrient channels [21] and/or extending the culture duration and system to examine larger constructs where the edges are further removed.…”
Section: Discussionmentioning
confidence: 99%
“… 4 In juvenile bovine chondrocytes, brief, rather than sustained, exposure to TGF-β at concentrations lower than the typically applied supraphysiological dose of 10 ng/mL was sufficient for robust cartilage tissue formation. 3 , 5 , 6 Other studies that used integrated experimental and computational approaches have shown that TGF-β stimulation can induce short-term graded responses ( Smad7 gene expression) that evolved into long-term switch-like responses (growth inhibition). 7 …”
Section: Introductionmentioning
confidence: 99%
“…Introducing channels into cell laden hydrogels is a common strategy to facilitate enhanced nutrient transfer while engineering large cartilage tissues. 19 , 21 , 33 36 Alginate was used as the hydrogel material as it has been shown to support robust MSC chondrogenesis and supports a rounded chondrocyte-like cell morphology. 37 39 …”
Section: Introductionmentioning
confidence: 99%